2013
DOI: 10.1136/annrheumdis-2012-203201
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of infliximab plus naproxen versus naproxen alone in patients with early, active axial spondyloarthritis: results from the double-blind, placebo-controlled INFAST study, Part 1

Abstract: ObjectivesTo assess whether combination therapy with infliximab (IFX) plus nonsteroidal anti-inflammatory drugs (NSAIDs) is superior to NSAID monotherapy for reaching Assessment of SpondyloArthritis international Society (ASAS) partial remission in patients with early, active axial spondyloarthritis (SpA) who were naïve to NSAIDs or received a submaximal dose of NSAIDs.MethodsPatients were randomised (2 : 1 ratio) to receive naproxen (NPX) 1000 mg daily plus either IFX 5 mg/kg or placebo (PBO) at weeks 0, 2, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
130
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(146 citation statements)
references
References 21 publications
3
130
0
13
Order By: Relevance
“…Conversely, 51.1% of the patients in the Infliximab as First-Line Therapy in Patients With Early Active Axial Spondyloarthritis Trial (INFAST) had a BASDAI50 response at week 28 after receiving a maximal dose of naproxen 1,000 mg daily. Consistent with the results of the present study, the mean BASDAI score reached 4.2, a decrease of 33%, at week 6 in these NSAID-treated patients (21). In the latter study, BASDAI50 response was not reported at earlier time points, rendering a head-to-head comparison difficult.…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, 51.1% of the patients in the Infliximab as First-Line Therapy in Patients With Early Active Axial Spondyloarthritis Trial (INFAST) had a BASDAI50 response at week 28 after receiving a maximal dose of naproxen 1,000 mg daily. Consistent with the results of the present study, the mean BASDAI score reached 4.2, a decrease of 33%, at week 6 in these NSAID-treated patients (21). In the latter study, BASDAI50 response was not reported at earlier time points, rendering a head-to-head comparison difficult.…”
Section: Discussionsupporting
confidence: 90%
“…Although a validated definition of clinical remission or LDA for BASDAI is currently unavailable 23 , certain cutoffs have been used in clinical trials and observational studies (BASDAI < 4 24 ; < 3 or ≤ 3) 25,26,27 . For example, in the INFAST study, 76% of patients with early axSpA receiving infliximab plus naproxen achieved a BASDAI < 3 at Week 28 9 . ASDAS offers a more objective assessment of disease activity because it includes C-reactive protein (CRP), which is a marker of inflammation, and may predict structural progression 28 .…”
mentioning
confidence: 99%
“…In 2001, the Assessment of Spondyloarthritis international Society (ASAS) developed a preliminary definition of clinical remission-ASAS partial remission (ASAS PR), which includes assessment of 4 domains: patient global, spinal pain, physical function, and "inflammation" (a proxy for true inflammation, based on morning stiffness) 5 . In clinical trials, 12-15% 5,6 of patients with ankylosing spondylitis (AS) receiving nonsteroidal antiinflammatory drugs (NSAID) achieve partial remission; a ceiling of ~15-40% at 6 months also exists with biologic therapies, including tumor necrosis factor (TNF) inhibitors and secukinumab 7,8 (Table 1 [9][10][11][12][13][14][15][16][17][18][19][20] ). Treating patients with short symptom duration may increase the proportion of patients reaching clinical remission to ~50% 9,21,22 .…”
mentioning
confidence: 99%
“…Numerous other studies have afterwards underlined the efficacy of using Infliximab in AS, not only clinically, but also by the reduction of inflammation visualized using MRI and also functionally, the effects being sustained, over periods exceeding 8 years [11]. Furthermore, Infliximab has been proven to be efficient also in non-radiographic AS, as shown on a subgroup of the patients in the INFAST study [12].…”
mentioning
confidence: 94%